Sex differences in adiposity and hemodynamic parameters as cardiovascular risk indicators among South African university staff: a descriptive cross-sectional study - Sibusiso Gogoba; Samuel Oluwaseun Olojede; Babatunde Adebola Alabi; Sodiq Kolawole Lawal; Odey Akpa; Ayoola Isaac Jegede; Onyemaechi Okpara Azu (BMC Cardiovascular Disorders)
Abstract Background Cardiovascular diseases (CVDs) are the leading cause of death worldwide, with their prevalence continuing to rise each year. Adiposity indexes and hemodynamic parameters have been established as effective predictors of CVDs when analysed separately. However, the impact of sex differences on the distribution and combined use of these predictors remains largely unexplored, particularly in Sub-Saharan Africa. This study aimed to investigate the sex differences in the distribution of adiposity indexes (AI) and hemodynamic parameters (HP), as well as their associated indicators of cardiovascular diseases risks among staff members at Walter Sisulu University (WSU). Methods This cross-sectional descriptive quantitative study was conducted on 100 healthy adults (50 males, 50 females) aged 18–65 years. AI were assessed using a stadiometer, body composition monitor, and tape measure, while HP were measured with a stethoscope and sphygmomanometer. Results The study’s findings revealed that mean values for AI, including height, visceral adiposity index, and waist circumference, were higher in males compared to females, while weight, body mass index, and hip circumference were greater in females. Additionally, the study indicated that mean values for HP, such as systolic blood pressure, diastolic blood pressure, and mean arterial pressure, were elevated in males, whereas pulse pressure was higher in females. Notably, heart rate was consistent across both sexes. Conclusion This study provides useful information about the sex-based patterns of adiposity indices and hemodynamic distribution among selected South African populations.